(3GdEYdGe hGdbGfhf aj GdGJaGbjGJ GdGbdjejI h GdOhdjI h OhQgeG aj GdJhYjI GdGLJeGYjI h ecGaMI GdLQjeI s - (3SejQ YGeQ Ydi(B, (3GdOdjejs ((3YeGf (B:s (3OGQ GdKbGaI(B,s, 2017)
(3fTCI hJWhQ GdEYdGe, eGgjJg, hXGFag hCSHGH hYhGed fLGMg haTdg, cPdc CfhGYg, hSGFdg, eUGOQg , ceG JfGhd eUGOQ bGfhf GdEYdGe hbjhO MQjJg aj GdGJaGbjGJ GdOhdjI h CNjQG JMOK Yf ecGaMI GdLQjeI hGdSdhc GdELQGej aj hSGFd GdEYdGe hGdbGfhf hMeGjI GdUMajjf aj GdbGfhf GdOhdj (B.s
(3eUGOQ h eQGLY U(B.357s
Keywords: (3GdGJaGbjGJs; (3GdGYdGes; (3GdbGfhfs